Regulacja prawna pomocy społecznej w Polsce w okresie powojennym do 1989 roku - Cendrowicz, Dominika (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article’s aim is to examine the legal regulation of social welfare in Poland after World War II up to the year 1989. The article analyzes the legal position of beneficiaries of social welfare benefits in that period. The political situation in Poland after the end of World War II introduced changes in the perception of the pre-war system of social welfare. In the period of the Polish People’s Republic, social welfare was based on an incorrect legal basis and the legal position of beneficiaries of social welfare was not protected by law. Social welfare was transferred to the Ministry of Health and its organizational system was centralized. Such a situation lasted until the Act of 29 November 1990 on Social Welfare was passed. Theoretical and historical methods of legal research were used in this article.
Keywords: pomoc społeczna; świadczenia pieniężne; PRL; socjalizm; autorytaryzm